Assessing the Development of Self-Confidence in Socially Deprived Students: A Rasch Model Analysis - Tri Lestari; Nandang Rusmana; Ipah Saripah; Nahadi Nahadi; Tri Zahra Ningsih; Tri Lestari; Nandang Rusmana; Ipah Saripah; Nahadi; Tri Zahra Ningsih (Universitas Negeri Malang, 2026)
This research is motivated by the low confidence of students which can hinder academic, social, and emotional success. One of the factors that contribute to low self-confidence in adolescents is social deprivation, which refers to a lack of social interaction or a feeling of isolation in the surrounding environment. This study aims to develop an instrument to measure the confidence of students with social deprivation using the Rasch Model to obtain a valid and reliable measuring tool. A quantitative approach with a survey method through an online questionnaire was used in this study, with participants as many as 396 high school students in Pangandaran Regency who experienced social deprivation, selected through purposive sampling techniques. The instrument was developed based on Lindenfield's theory, covering aspects of inner confidence and innate confidence, and analyzed using the Rasch Model through Winsteps software version 3.73. The results of the study show that this instrument is valid and reliable, with a unidimensionality confirmed through raw variance explained of 48.1%. In addition, response categories 0 and 1 are well understood, supporting validity, while high reliability with Alpha Cronbach 0.89 and Person Reliability 0.87, as well as person-fit analysis show consistent responses. Thus, this instrument can be used to measure the self-confidence of students who experience social deprivation more accurately. The recommendations of this study include the implementation of instruments in guidance and counseling services in schools as well as follow-up research to test the effectiveness of psycho-cybernetics-based interventions in improving students' self-confidence with social deprivation.